Resistance Evaluation of Some Rice Varieties by Feeding Activity of Brown Planthopper Population in Java - Wayan Murdita; Suwarman; Ahmad Imroni; Willing Bagariang (Warmadewa University Press, 2021)
Brown Planthopper (BPH), Nilaparvata lugens Stal (Hemiptera: Delpachidae) is the important pest of rice. The infestation of BPH reduced the rice yield on rice producer countries in Asia. In Indonesia, the area of BPH infestation frequently fluctuated over the year. BPH directly caused hopper burn and also vector of rice grassy stunt virus (RGSV) and rice ragged stunt virus (RRSV). This study aimed to evaluate the resistance of some rice varieties to different BPH population in Java. Three BPH populations collected from Karawang (West Java), Pekalongan (Central Java) and Kendal (Central Java) were used in this study. The rice resistance was evaluated by conducting honeydew test. There were eight rice varieties tested i.e Sembada 168, Ciherang, Inpari 32, Inpari 33, IR 64, TN1, Ratu Heenati and PTB 33 with five replications. A number of 200 female adults (five females per plot) were starved for 2 hours before inserting to pot containing one seedling. The BPH adults were allowed to feed 40-day-old plants for 48 hours. The area of honeydew excreted by BPH was measured using software Image J. We used analysis of variance (ANOVA) and cluster analysis with ward method and similarity index of Euclidean distance to analyze the rice resistance to BPH. The study indicated three groups of rice resistance level. The variety of Sembada 168 and TN1 were susceptible to BPH. Variety of Ciherang, Inpari 32, Inpari 33 and IR 64 were moderately resistant to BPH. However, PTB 33 and Ratu Heenati were strongly resistant to BPH population of Java.